Second Order Limit Language Associated with Two Rules - Muhammad Azrin, Ahmad; Nor Haniza, Sarmin; Fong, Wan Heng; Yuhani, Yusof (Universiti Teknologi Malaysia, 2015)
The concepts of splicing system involve the study of cut and paste phenomenon of deoxyribonucleic acid (DNA). The splicing language, which is resulted from a splicing system, can be classified as inert persistent language, active persistent language and limit language. As one of the types of splicing language, limit language can biologically be referred as the remaining molecule after the process has attained its equilibrium state. In this paper, the existence of second order limit language is explored strictly using at most two initial strings and two rules. In addition, the actual biological examples are resented. By using the Y-G splicing system, the results obtained are then used to prove the existence of second order limit language in few classes of Y-G splicing system.